Membaca Strategi Eksistensi LGBT di Indonesia - Imron Muttaqin (Raheema, 2016)
LGBT is a deviance through mass media and social based, and specific researches about gender. Nonetheless, there is a hidden agenda to support some communities that argue their ontology, axiology, and epistemology. Furthermore, the narrative argument developed by pro LGBT side has considerably changed the human nature. Thus, this thought should be rectified wisely in order to avoid unnecessary issues. Moreover, based on the researches on the text media, LGBT promotes their activities through some ways. 1) Reinterpret the verses about LGBT by creating a counter-interpretation and bringing it up on the contemporary context. 2) Use the research based that is performed by the scientists to legalize their ideas. 3) Utilize the human rights as a legal protection. 4) Engage with gender issue as an initial point to catch the public opinion. 5) Handle the printed media. 6) Control the electronic media. 7) Work on social media.